2010
DOI: 10.1194/jlr.m006239
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of phospholipid transfer protein with human tear fluid mucins

Abstract: This article is available online at http://www.jlr.org well as an economic burden to patients and the community. DES is considered to arise from the interplay of inadequate tear production, increased tear evaporation, and altered composition of the tear fi lm. The underlying biochemical and physiological events in the development of DES and precise composition of the human tear fl uid are only partially understood. Until now the model of the tear fi lm has been a three-layered structure ( 2, 3 ): the inner muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Secreted mucins may have an active role in lipid organization at the surface of the tear film [296,509] and phospholipid transfer protein functions to scavenge lipophilic substances from ocular mucins [510], but data supporting a direct interaction between mucins and lipids are lacking. In the epithelial glycocalyx, the transmembrane mucins MUC1 and MUC16 bind galectin-3 to promote ocular surface barrier function [382].…”
Section: Biochemical Properties Of Tearsmentioning
confidence: 99%
“…Secreted mucins may have an active role in lipid organization at the surface of the tear film [296,509] and phospholipid transfer protein functions to scavenge lipophilic substances from ocular mucins [510], but data supporting a direct interaction between mucins and lipids are lacking. In the epithelial glycocalyx, the transmembrane mucins MUC1 and MUC16 bind galectin-3 to promote ocular surface barrier function [382].…”
Section: Biochemical Properties Of Tearsmentioning
confidence: 99%
“…Understanding of tear mucin regulation may produce insight into the mechanism of at least some types of dry eye [ 49 ]. Phospholipid transfer protein, a protein that interacts with mucins, may also be relevant to the dry eye mechanism [ 104 ], but this has not been studied well enough to be used for clinical purposes. Since the regulation of mucin affects dry eye pathologic mechanisms, it gives greater credibility to the use of mucins as a marker for this disease.…”
Section: Reviewmentioning
confidence: 99%
“…enhanced levels of these lipids. It has been shown that both lipocalin ( 29 ) and phospholipid transfer protein ( 30 ) in human tears serve to scavenge lipids from corneal surfaces to ensure a "wettable" cornea. Specifi cally, it was stated that phospholipid transfer protein knockout mice developed appreciable DES and elevated corneal epithelial permeability ( 30 ), which is also in accordance with the accumulation of phospholipids in DES observed in our study.…”
Section: Levels Of Wes Were Altered In Des In a Manner Dependent On Tmentioning
confidence: 99%